Simulated GI digestion of dietary protein: Release of new bioactive peptides involved in gut hormone secretion. (November 2016) - Caron, Juliette; Cudennec, Benoit; Domenger, Dorothée; Belguesmia, Yanath; Flahaut, Christophe; Kouach, Mostafa; Lesage, Jean; Goossens, Jean-François; Dhulster, Pascal; Ravallec, Rozenn
Abstract: Dietary proteins have been reported to induce a strong feeling of satiety that has been partially explained by gut hormone level increase. Up to date, various protein hydrolysates have demonstrated in vitro and in vivo their potential to stimulate gut hormone secretion related to food intake decrease and their mechanisms of action have just started to be resolved. In this context, this study aimed at identifying new peptide sequences involved in gut hormone secretion released by protein in vitro gastrointestinal digestion. Targeted gut hormones were Cholecystokinin (CCK) and Glucagon-Like Peptide 1 (GLP-1). The activity of DPP-IV was also considered as it strongly modulates GLP-1 action. In a previous study, simulated digestion of dietary protein has generated hydrolysates with enhancing effect on CCK and GLP-1 secretion in STC-1 cells as well as DPP-IV inhibitory properties. Successive purification steps were performed to isolate peptide fractions involved in these bioactivities whose sequence was determined by LC-MS-MS. Three peptide sequences ANVST, TKAVEH and KAAVT were pointed out for their stimulating effects on GLP-1 secretion. The sequence VAAA was isolated for its DPP-IV inhibitory properties. Two peptide groups were strongly involved in CCK release sharing a certain occurrence of aromatic amino acid residues. Graphical abstract: Highlights: Dietary peptides activate short term signals regulating energy homeostasis. Three new peptide sequences were identified with GLP-1 enhancing properties. One new peptide sequence was identified as DPP-IV inhibitor. Peptides with CCK enhancing properties were enriched with aromatic residues.